Growing up with chronic renal disease - The road remains rocky - Rodrigues,Natacha (2015)
Background: Understanding the aetiology and approach to management of chronic kidney disease presenting in the paediatric age range continues to represent a true challenge. With the improvement of paediatric care, the number of patients reaching adulthood has increased in recent decades, and it is well known that the transition period from paediatric to adult care is critical; it is associated with a high rate of dropout from care, making it imperative to have an organized system. Methods: Hospital Santa Maria has followed a transition model for the last 17 years in order to optimize medical care for patients with chronic kidney disease who reach adulthood before progressing to end-stage renal disease (ESRD). From 1998 to 2013, our unit has managed 151 such patients. We retrospectively analysed this population with regard to their demographic data, renal diagnosis, follow-up and outcomes. Results: The most prevalent pathologies were uropathies (61 patients), glomerulopathies (46 patients), tubulopathies (18) and cystic diseases (seven), with other causes found in 15 patients. Each group was char- acterized individually. The mean annual decrease of the glomerular filtration rate (GFR) was 2.4ml/ min/1.73m2/year. Fourteen patients developed end-stage renal disease, four were transferred to other hospitals and 18 dropped-out. Eighty-six per cent had finished high school, 60% were working, 32% were students and 8% were unemployed. Conclusion: The aetiology of renal disease presenting in paediatric age is singular. Our dropout rate and annual decrease of GFR are lower than in units with no transition model. The majority of patients choosing haemodialysis had a previous mature fistula. More studies are needed